2004
DOI: 10.1063/1.1738640
|View full text |Cite
|
Sign up to set email alerts
|

Computing time scales from reaction coordinates by milestoning

Abstract: An algorithm is presented to compute time scales of complex processes following predetermined milestones along a reaction coordinate. A non-Markovian hopping mechanism is assumed and constructed from underlying microscopic dynamics. General analytical analysis, a pedagogical example, and numerical solutions of the non-Markovian model are presented. No assumption is made in the theoretical derivation on the type of microscopic dynamics along the reaction coordinate. However, the detailed calculations are for Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
719
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(727 citation statements)
references
References 8 publications
6
719
0
2
Order By: Relevance
“…An algorithm to determine the time scales of complex processes following predetermined milestones along the reaction coordinate was recently developed but has not been tested yet on complex biomolecular processes. 72 , was used to retain the coordinates of protein residues and DNA sequences in place during these preparations. The hydroxyl group was also added to the 3′ terminus of the primer DNA strand.…”
Section: Sdelmentioning
confidence: 99%
“…An algorithm to determine the time scales of complex processes following predetermined milestones along the reaction coordinate was recently developed but has not been tested yet on complex biomolecular processes. 72 , was used to retain the coordinates of protein residues and DNA sequences in place during these preparations. The hydroxyl group was also added to the 3′ terminus of the primer DNA strand.…”
Section: Sdelmentioning
confidence: 99%
“…In this paper we have shown that this exit probability has intrinsic value and can allow for the precise computation of the statistics of switching times, escape times and completion times for more complicated trajectories. Unlike previous analyses of stochastic switch rates that utilize Monte Carlo type approaches [12][13][14][15][16][17], the current method directly approximates the transient solution to the master equation and provides otherwise unachievable precision guarantees on the switch time distribution. At present this precision comes at a cost of adverse complexity scaling.…”
Section: Resultsmentioning
confidence: 99%
“…As a few representative examples, these methods include Transition Path Sampling [12], Transition Interface Sampling [13], and various approaches of transition path sampling with multiple interfaces [14][15][16][17]. By concentrating on trajectories that eventually result in switches and interrupting the the vast majority trajectories that do not, these approaches are far more efficient than a standard brute force Monte Carlo approach like the SSA.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, to complete this study with a look at the rates for each folding stage, one would need to reintroduce a time scale to the trajectories. This can be accomplished by the Milestoning technique 43 currently available for use in the MOIL package.…”
Section: Chapter 6 Conclusionmentioning
confidence: 99%